2018
DOI: 10.5009/gnl18111
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Nucleic Acid Probe-Based Analysis as a New Detection Method for Clarithromycin Resistance inHelicobacter pylori

Abstract: Background/AimsHelicobacter pylori eradication rates are decreasing because of increases in clarithromycin resistance. Thus, finding an easy and accurate method of detecting clarithromycin resistance is important.MethodsWe evaluated 70 H. pylori isolates from Korean patients. Dual-labeled peptide nucleic acid (PNA) probes were designed to detect resistance associated with point mutations in 23S ribosomal ribonucleic acid gene domain V (A2142G, A2143G, and T2182C). Data were analyzed by probe-based fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…The critical essence of these two mutations in incurring resistance on susceptible H pylori strains has also been proven by site‐directed mutagenesis 57 . Again, in agreement with others, 58‐60 in our limited number of resistant strains, we have also found the mentioned mutations, as the major (8/11) cause of CLA resistance. We have also detected other mutations (T2182C, T2656A, and G2569C), which were outside of the drug‐interacting region and thus did not undergo our molecular docking studies.…”
Section: Discussionsupporting
confidence: 90%
“…The critical essence of these two mutations in incurring resistance on susceptible H pylori strains has also been proven by site‐directed mutagenesis 57 . Again, in agreement with others, 58‐60 in our limited number of resistant strains, we have also found the mentioned mutations, as the major (8/11) cause of CLA resistance. We have also detected other mutations (T2182C, T2656A, and G2569C), which were outside of the drug‐interacting region and thus did not undergo our molecular docking studies.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, PNA probe‐based qPCR allows easy interpretation of mutation type using a graph of the melting peak. It has recently been reported that the same PNA probe‐based qPCR kit used in this study shows 100% positive predictive value and high κ‐value for detecting the presence and mutation status of H pylori in cultured H pylori samples isolated from Korean patients when compared to conventional PCR with sequencing analysis . Taken together, the PNA probe‐based qPCR method is a simple and accurate method for detection of H pylori in gastric biopsies.…”
Section: Discussionsupporting
confidence: 51%
“…The quasi-species development of H. pylori in a single host might result in treatment failure even after a tailored eradication strategy based on the presence of a 23S ribosomal RNA point mutation[28]. Second, a DPO-PCR-based evaluation is limited to detecting mutations of A2142G and A2143G in 23S rRNA, and other mutations, such as the A2144G or A2142C mutation of H. pylori , cannot be detected[20,30].…”
Section: Discussionmentioning
confidence: 99%